THE ROLE OF ONCOGENIC TYPES OF THE HUMAN PAPILLOMAVIRUS IN THE DEVELOPMENT OF PRECANCEROUS CONDITIONS AND CERVICAL CANCER - Sodikjonova Shokhsanam; Rajabova Nodira; Karimova Nargiza Mansurovna (Western European Studies, 2025)
Persistent infection with oncogenic, high-risk human papillomavirus is the necessary etiologic driver of virtually all cervical cancers, yet only a small fraction of infections progress to clinically significant precancer or invasive malignancy. This review synthesizes current evidence on how carcinogenic HPV genotypes, especially HPV16 and HPV18 and several additional high-risk types, contribute to the natural history of cervical intraepithelial neoplasia and adenocarcinoma in situ, and ultimately to invasive cervical cancer. We discuss genotype-specific differences in carcinogenic potential, viral and host mechanisms that promote persistence and malignant transformation, and the stepwise biological continuum from transient infection to high-grade precancer. The central molecular events include expression of E6 and E7 oncoproteins that disrupt p53 and retinoblastoma tumor suppressor pathways, remodeling of the cellular epigenetic landscape, immune evasion, and, in many cancers, viral DNA integration with sustained oncoprotein expression.
Keywords: human papillomavirus; high-risk HPV; HPV16